The Results of Unfinished Storytelling Activities for the Development of Computational Thinking and Coding in Early Childhood - Yonwilat, Chuleekorn; Sawangchareon, Pensri; Butkatunyoo, Oraphan (Interdisciplinary Academic and Research Journal, 2023)
The results of unfinished storytelling activities for the development of computational thinking and coding in early childhood, the purpose of this research was to compare the computational thinking and coding of early childhood children before and after receiving the unfinished storytelling activities. The target group was 23 male and female children aged between 4 - 5 years old, studying in kindergarten level 2, semester 2, the academic year 2022, Watpunjathayikawas School under the Pathumthani Primary Educational Service Area Office 2, Ministry of Education. The research tools used in the study were 24 plans of unfinished storytelling activities for developing computational thinking and coding in early childhood and an assessment form of computational thinking and coding in early childhood. Data were analyzed by mean, standard deviation, and content analysis. The study’s results revealed that early childhood children who received unfinished storytelling activities had higher post-experimental computational thinking and coding averages than before the experiment. The average score before the experiment was 13.30, and the standard deviation was 4.47, after the experiment, the average score was 25.08, and the standard deviation was 3.21. It was found that the most developed aspect is the algorithm and coding, followed by decomposition, pattern recognition, and abstraction respectively.